1995
DOI: 10.1016/0954-6111(95)90008-x
|View full text |Cite
|
Sign up to set email alerts
|

Salmeterol and formoterol in partially reversible severe chronic obstructive pulmonary disease: a dose-response study

Abstract: When testing the response to beta 2-agonist drugs in severe chronic obstructive pulmonary disease (COPD), a dose-response assessment should be undertaken. This study compares the time course of inhaled salmeterol (25, 50 and 75 micrograms) and formoterol (12, 24 and 36 micrograms) at different doses in a group of 12 patients with partially reversible, but severe COPD (FEV1 of 12-32% of predicted values after beta 2-agonist drugs had been withheld for 24 h). All doses of salmeterol and formoterol induced a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
2
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(69 citation statements)
references
References 16 publications
3
63
2
1
Order By: Relevance
“…The results demonstrate that, in patients with stable COPD and severe airflow obstruction, 50 mg of salmeterol produces a significant improvement in lung function as assessed by FEV1 and sGaw, with a peak effect after 2±4 h and a duration of action of $12 h. In addition, the combination of salmeterol 50 mg and ipratropium bromide 40 mg elicited a greater bronchodilator response than salmeterol alone during the first 6 h after inhalation. The present results with salmeterol are in line with those of CAZZOLA et al [4]. These authors, comparing single doses of 25, 50 and 75 mg salmeterol in patients with COPD, found that all doses induced a significant improvement in FEV1 over the 12 h monitoring period.…”
Section: Discussionsupporting
confidence: 92%
“…The results demonstrate that, in patients with stable COPD and severe airflow obstruction, 50 mg of salmeterol produces a significant improvement in lung function as assessed by FEV1 and sGaw, with a peak effect after 2±4 h and a duration of action of $12 h. In addition, the combination of salmeterol 50 mg and ipratropium bromide 40 mg elicited a greater bronchodilator response than salmeterol alone during the first 6 h after inhalation. The present results with salmeterol are in line with those of CAZZOLA et al [4]. These authors, comparing single doses of 25, 50 and 75 mg salmeterol in patients with COPD, found that all doses induced a significant improvement in FEV1 over the 12 h monitoring period.…”
Section: Discussionsupporting
confidence: 92%
“…Each patient was requested to discontinue all bronchodilating medications starting from at least 24 h before execution of the test [12][13][14]. All subjects performed two types of manoeuvres: no.…”
Section: Methodsmentioning
confidence: 99%
“…(6) Therefore, COPD patients presenting a poor response to short-acting β 2 -agonists might present significant reversibility to formoterol, with considerable improvement in lung function and relief of symptoms. (4,6,24) Functional changes can be seen for weeks after the baseline testing and might be associated with several variables involved in the therapeutic efficacy of the drug. (23,24) In a study involving 20 patients with partially reversible COPD and similar to the present study in design (formoterol and a placebo were compared), a significant response was observed even within 10 or 20 min after formoterol administration.…”
Section: Discussionmentioning
confidence: 99%
“…(4,6,24) Functional changes can be seen for weeks after the baseline testing and might be associated with several variables involved in the therapeutic efficacy of the drug. (23,24) In a study involving 20 patients with partially reversible COPD and similar to the present study in design (formoterol and a placebo were compared), a significant response was observed even within 10 or 20 min after formoterol administration. (25) In our study, patients with stable COPD presented a substantial improvement in FEV 1 at 30 min after formoterol administration, indicating that formoterol has an immediate bronchodilator effect.…”
Section: Discussionmentioning
confidence: 99%